Reversible Aphasia in Adolescence: A Late-Onset form of Landau Kleffner Syndrome? Report of a Single Case - Gianfranco Denes; Cristina Mantovan; Emilia Ferruzza; Carlo P. Trevisan; Antonia Gallo (Behavioural Neurology)
An adolescent boy developed a long-lasting pattern of global aphasia, concomitant to focal (left temporal) EEG abnormalities; this was followed by complete recovery. Laboratory and neuroimaging studies were within normal limits. The possibility of a late-onset Landau Kleffner syndrome is discussed.